The Effect of Servant Leadership on Employee Performance with Employee Engagement and Organizational Citizenship Behavior (OCB) As A Mediation Variable in Mandiri Inhealthth - Pardi Simamora; I Ketut Sudiarditha; Corry Yohana (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
Many companies in this era of openness and globalization offer products and services with relatively the same characteristics. This condition creates increasingly high competition in the business world, causing the business world to become very competitive, a business climate that is always changing and uncertain . This study analyzes the effect of servant leadership on employee performance with employee engagement and organizational citizenship behavior as mediating variables in Mandiri Inhealth companies. Determination of the sample using proportionate stratified random sampling method . The sample in the study amounted to at least 154 respondents but collected 206 respondents were analyzed usingStructural Equation Modeling (SEM). The results of the study are there is a direct effect on servant leadership on employee performance, there is a direct effect on servant leadership on employee engagement , there is a direct effect on employee engagement on employee performance, there is a direct effect on servant leadership on organizational citizenship behavior , there is a direct effect on organizational citizenship behavior on employee performance, there is no indirect effect of servant leadership on employee performance through employee engagement mediation , there is an indirect effect of servant leadership on employee performance through mediating organizational citizenship behavior.